Careers in Science and Engineering: A Student Planning Guide to Grad School and Beyond.
Presents "Careers in Science and Engineering: A Student Planning Guide to Grad School and Beyond," published by the National Academy Press in Washington, D.C. The guide helps undergraduate and graduate students in science, engineering, and mathematics to make career and educational choices.